DOI: 10.11606/t.43.2010.tde-16092010-102755
|View full text |Cite
|
Sign up to set email alerts
|

Evolução de Buracos Negros Primordiais no Universo

Abstract: a lei de Stefan-Boltzmann válida pelo princípio da equivalência. 8 Ver capítulo 2 para uma discussão.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 113 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…The off-diagonal term, together with the fact that G r r and G θ θ have to be equal, puts a stringent constraint on the choice of fluid. If a single perfect fluid is used as a source for this metric, the equality of the diagonal terms implies that the fluid has to be comoving [23]. This in turn implies that the off-diagonal term is zero, and therefore that ṁ has to vanish.…”
mentioning
confidence: 99%
“…The off-diagonal term, together with the fact that G r r and G θ θ have to be equal, puts a stringent constraint on the choice of fluid. If a single perfect fluid is used as a source for this metric, the equality of the diagonal terms implies that the fluid has to be comoving [23]. This in turn implies that the off-diagonal term is zero, and therefore that ṁ has to vanish.…”
mentioning
confidence: 99%
“…(a) McVittie metric (15) with constant mass In both examples, the expansion is given by Eq. (31). Note that, in this class of metrics, the null infinity I + is space-like.…”
Section: A Einstein Equationsmentioning
confidence: 93%
“…A seminal step in this direction arXiv:1408.5538v1 [gr-qc] 24 Aug 2014 was taken when a generalized version of the McVittie metric was introduced with an arbitrary time-dependent mass [27], which generalized the Sultana-Dyer black hole [28] (in its turn obtained via a conformal transformation of the Schwarzschild metric), and was later applied to the problem of dark-energy accretion [29]. The specific form of the mass function could then in principle be obtained from the field equations, or from some hydrodynamic model for the source, which no longer could be taken to be a single perfect fluid [30] or a superposition of multiple perfect fluids [31], so a more general approach was needed. The needed step forward arrived when it was found that in the fluid interpretation the accretion (or evaporation) rate could be explained by the introduction of a heat-flow term associated to the presence of a temperature gradient via a Landau-Eckart model [32], as other viscous terms vanish due to the high degree of symmetry of the metric.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation